Investigation of the effect of serotonin-activated semen washing medium on sperm motility at the molecular level: a pilot study - Moshfeghi, Elnaz; Yilmazer, Yasemin; Dogan, Sinem; Aydin, Turgut; Findikli, Necati; Ozbek, Tulin (CAMBRIDGE UNIV PRESS, 2024)
In Assisted Reproductive Technologies (ART), efficient sperm preparation is vital for successful fertilization, with washing media enhancing the process. This pilot study examines the molecular-level impact of a new serotonin-containing sperm-washing medium (Prototype) on sperm motility and ROS metabolism, comparing it with commercially available media (Origio and Irvine). Semen samples from thirty-one individuals underwent preparation using the swim-up method post-semen analysis. Each sample was separately washed with the Prototype, Origio and Irvine mediums. ROS formation was determined through flow cytometric, and AT2R and PRDX2 protein levels, associated with sperm motility, were assessed via Western blot. Statistical evaluation compared the findings among the three outlined media. Significant differences were found among three washing media in terms of total and progressive motility. The Prototype medium showed the highest increase in both total (66%) and progressive motility (59%), while the control group exhibited the lowest increases (41% and 27.7%, respectively). Regarding ROS levels, the prototype (11.5%) and Origio (10.7%) groups demonstrated a notable decrease, contrasting with Irvine (25.8%). Molecular assessment revealed a significant elevation in AT2R protein levels in the prototype medium (59%), compared to other media. Additionally, an increase in PRDX2 protein levels was observed in the prototype medium, although this didn't reach statistical significance. Serotonin-activated washing media for sperm preparation can be a suitable choice for selecting high-quality sperm in ART. A broader molecular analysis with a larger sample size is required to explore the mechanisms and effectiveness of using a serotonin-containing sperm-washing medium in routine ART.
Keywords: AT2R; infertility; PRDX2; ROS; serotonin; sperm motility; ANGIOTENSIN-II RECEPTORS; PROTEIN-KINASE-A; OXIDATIVE STRESS; SUPPLEMENTATION; CAMP; Cell Biology; Developmental Biology; Reproductive Biology